Menyegarkan Kembali Pemahaman Teori Demokrasi dalam Wacana Ketatanegaraan Melalui Pemikiran Hans Kelsen - Sobirin Malian (Supremasi Hukum: Jurnal Kajian Ilmu Hukum, 2012)
Sustainability of a country necessitates the existence of a strong constitutional rule. State based on democracy, according to Hans Kelsen requires people that agree on the meaning of democracy, as well as understand the workings of democracy and its usefulness to their lives. A strong democratic is rooted from will of people and aims to achieve shared welfare. Democracy must be related to the will of the people. Therefore, the socialization of the growth and development of understanding for democracy is necessary to be continued for the community, especially for people who live in developing countries. In constitutional discourse developed by Hans Kelsen, the problem of democratic process leads to accountability of government, legislature and judiciary institution from electorate.